IMPLEMENTASI STRATEGIS MANAJEMEN SUMBER DAYA MANUSIA PERSPEKTIF AL-QUR’AN - Fantika Vera Entrisnasari; Fantika Febry Puspitasari; Supriyanto Supriyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
Indonesia is predicted to experience a demographic bonus between 2015 and 2035. With the abundance of productive human resources, Islamic education institutions must be ready to manage their human resources with the right strategy to implement. Management of human resources from Al-Quran's perspective is the right choice in an Islamic educational institution, and this management has been implemented in integrated Islamic schools. In this research, a case study will be taken at SDIT Insan Cendekia Boyolali, which is considered useful in implementing human resource management. The implementation carried out by SDIT Insan Cendekia Boyolali starts from four management components: 1) Planning, 2) Organizing, 3) Controlling, 4) Actuating has implemented Al-Qur'an perspective management. Likewise, in the implementation of the principles of human resource management, namely: 1) The principle of monotheism, 2) The principle of justice and welfare, 3) The principle of deliberation, 4) The principles of efficiency, effectiveness, and productivity, 5) The principles of discipline, integrity, and loyalty, 6) The principle of division of authority and responsibility, 7) The Ukhuwah Principle. There are still some deficiencies in the implementation, but educators can already felt the results.